2013
DOI: 10.3390/v5051325
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Cytomegalovirus Latency and Reactivation

Abstract: Cytomegalovirus (CMV) gene expression is repressed in latency due to heterochromatinization of viral genomes. In murine CMV (MCMV) latently infected mice, viral genomes are bound to histones with heterochromatic modifications, to enzymes that mediate these modifications, and to adaptor proteins that may recruit co-repressor complexes. Kinetic analyses of repressor binding show that these repressors are recruited at the earliest time of infection, suggesting that latency may be the default state. Kidney transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 111 publications
(165 reference statements)
2
55
0
Order By: Relevance
“…IE-3 is the MCMV functional homologue of HCMV IE-2, which is the major transactivator of early gene expression (Angulo et al, 2000;Keil et al, 1987aKeil et al, , 1987bMartínez et al, 2010;Messerle et al, 1992). We previously showed that allogeneic transplantation induced reactivation of IE gene expression 48 h after transplant, and that RNA polymerase phosphorylated at Ser2 (Pol II pS2) was recruited to both the MIEP and the IE-3 coding region (Hummel et al, 2001;Liu et al, 2013). Here, we show that IE-3 RNA expression was detectable by reverse transcriptase-qPCR at 48 h, but not at 3 or 24 h post-transplant ( Fig.…”
Section: Nf-k B and Ap-1 Family Members Are Differentially Regulated supporting
confidence: 49%
See 4 more Smart Citations
“…IE-3 is the MCMV functional homologue of HCMV IE-2, which is the major transactivator of early gene expression (Angulo et al, 2000;Keil et al, 1987aKeil et al, , 1987bMartínez et al, 2010;Messerle et al, 1992). We previously showed that allogeneic transplantation induced reactivation of IE gene expression 48 h after transplant, and that RNA polymerase phosphorylated at Ser2 (Pol II pS2) was recruited to both the MIEP and the IE-3 coding region (Hummel et al, 2001;Liu et al, 2013). Here, we show that IE-3 RNA expression was detectable by reverse transcriptase-qPCR at 48 h, but not at 3 or 24 h post-transplant ( Fig.…”
Section: Nf-k B and Ap-1 Family Members Are Differentially Regulated supporting
confidence: 49%
“…CMV genomes are heterochromatinized and the IE genes, which are required for lytic replication, are transcriptionally silent in latent infection (Grzimek et al, 2001;Hummel et al, 2001;Kurz et al, 1997Kurz et al, , 1999Liu et al, 2008Liu et al, , 2010Seckert et al, 2013;Simon et al, 2005). Activation of IE gene expression, through recruitment of transcription factors that control MIEP activity and remodelling of viral chromatin, is therefore likely required for reactivation of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations